Effects of meloxicam and etoricoxib on blood pressure and vascular reactivity in rats - Trongtorsak, Petcharat; Sukpat, Supakanda; Buapool, Doungnapa; Thornorla, Karuna (Chulalongkorn Medical Journal, 2023)
Background : Treatment with selective cyclooxygenase-2 (COX-2) inhibitor is associated with increased risk of cardiovascular events. Inhibition of COX-2 reduces vascular prostacyclin synthesis without disrupting COX-1-derived thromboxane synthesis, which may alter vascular tone and responsiveness. Objective : To examine the effects of two COX-2 inhibitors, meloxicam and etoricoxib, on blood pressure and vascular reactivity in rats. Methods : Unconscious blood pressure was obtained from Sprague Dawley rats by a tail-cuff method, and then the rats were divided into 3 groups (n = 9 in all groups): 1) non–treated control, 2) meloxicam 1 mg/kg/d, 3) etoricoxib 3 mg/kg/d. Drugs were orally administered 4 times/week in a consecutive day for 6 weeks. At the end of the treatments, unconscious blood pressure and pulse wave velocity (PWV, an index of arterial compliance) were determined. Thoracic aorta was isolated for the assessment of vascular responses to phenylephrine (PE, α-adrenoceptor agonist; 10-10–10-6 M), isoproterenol (Iso, β-adrenoceptor agonist; 10-8–10-4 M), and acetylcholine (Ach, muscarinic receptor agonist; 10-9–10-5 M). Results : Etoricoxib caused a more pronounced effect on body weight gain than meloxicam, suggesting its greater effect on body fluid. Both COX-2 inhibitors did not alter PWV, indicating no change in arterial compliance. The systolic pressure, diastolic pressure and mean arterial pressure of etoricoxib group, but not meloxicam group, showed non-significantly higher than those of control group. The responsiveness of aortic rings to PE and Ach were not altered by either meloxicam or etoricoxib treatment. However, both drug treatments caused a significantly greater vasorelaxation responses to Iso (P <0.05). Conclusions : These results show that etoricoxib, but not meloxicam, has a nonsignificant increasing blood pressure which may be associated with body fluid retention. Both COX-2 inhibitors enhance β-adrenoceptor vasodilation.